The complete mitochondrial genome of Conwentzia sinica (Neuroptera: Coniopterygidae). Issue 2 (3rd July 2019) - Song, Jialu; Dong, Jiayu; Ma, Mingwei; Yi, He; Liu, Zhiqi
Abstract: The complete mitochondrial genome (mitogenome) of Conwentzia sinica Yang, 1974 was sequenced and analyzed. The sequenced mitogenome is 15, 153 bp in size, including 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes, and one control region. Thirteen PCGs use ATN as the start codon. Most of PCGs terminate with TAA codons but ND5, ND4 with a single T residue, and ND3 terminates with TAG. The lrRNA gene is 1290 bp. The measured length of srRNA gene is 782 bp. Twenty-two tRNA genes possess the typical clover-leaf secondary structure except for tRNA Ser(AGN) . The phylogenetic result supports the monophyly of the family Coniopterygidae and a closer relationship between Conwentzia and Coniopteryx .